Economic evaluation of the manufacturing of 3D-printed wrist orthoses vs low temperature thermoplastic wrist orthoses - Marianne von Haller; Louise Couchman; Philipp Honigmann (3D Printing in Medicine)
Abstract Background In recent years, three-dimensional (3D) printing has emerged as a new manufacturing technique of custom-fitted orthoses, showing comparable stability, and wearing comfort than traditional orthoses. However, there is a paucity of data on economic aspects of the manufacturing of 3D-printed orthoses (3DPOs). The aim of this study is to economically evaluate the manufacturing process of 3DPOs compared to conventional low-temperature thermoplastic orthoses (LTTOs) in a clinical setting. Methods A prospective cost minimisation analysis from a healthcare provider perspective was conducted including 17 wrist orthoses (8 3DPOs and 9 LTTOs). Results The mean cost per orthosis was significantly higher in 3DPOs (€ 46.54) than in LTTOs (€ 30.28). The main cost factors in 3DPOs were the labour (62.2%) and purchase cost (22.2%), while the material (69.4%) and labour cost (30.6%) were most important in LTTOs. Conclusions The high initial investment might be a hurdle in the implementation of 3DPOs in hand rehabilitation, however, lower material cost and less waste is a benefit compared to LTTOs. Large-scale use of the infrastructure and developments in technology might reduce the investments needed in the future. Trial registration : not applicable.